2005
DOI: 10.1051/0004-6361:20041811
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical state and star formation properties of the merging galaxy cluster Abell 3921

Abstract: Abstract. We present the analysis and results of a new VRI photometric and spectroscopic survey of the central ∼1.8×1.2 Mpc 2 region of the galaxy cluster A3921 (z = 0.094). We detect the presence of two dominant clumps of galaxies with a mass ratio of ∼5: a main cluster centred on the Brightest Cluster Galaxy (BCG) (A3921-A), and an NW sub-cluster (A3921-B) hosting the second brightest cluster galaxy. The distorted morphology of the two sub-clusters suggests that they are interacting, while the velocity distr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
5

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 74 publications
8
95
5
Order By: Relevance
“…One of the variants of this method establishes a relationship between the total mass M of the bimodal cluster and the angle α between the plane of the sky and the collision axis of the two clumps (Barrena et al 2002;Ferrari et al 2005). The input parameters derived from the observations are the relative radial velocity between the two subclusters V r and their projected spatial separation R p .…”
Section: Two-body Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…One of the variants of this method establishes a relationship between the total mass M of the bimodal cluster and the angle α between the plane of the sky and the collision axis of the two clumps (Barrena et al 2002;Ferrari et al 2005). The input parameters derived from the observations are the relative radial velocity between the two subclusters V r and their projected spatial separation R p .…”
Section: Two-body Analysismentioning
confidence: 99%
“…The aims of the program are to characterize the merging scenario (epoch of collision, geometry, and mass ratios) and to test the impact of the merging process on the properties of galaxies, in particular the star formation. For example, the combined X-ray and optical analysis allowed us to determine the merging scenario of the first two clusters (a premerger for A1750, Belsole et al 2004; and a recent post-merger for A3921, Belsole et al 2005;Ferrari et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We produced density maps of the bi-dimensional galaxy distribution of each observed cluster on the basis of a multi-scale approach, as described in Ferrari et al (2005). To avoid projection effects as much as possible, we selected galaxies lying on the cluster red-sequence and brighter than L * + 3.…”
Section: New Detections Of Diffuse Radio Emissionmentioning
confidence: 99%
“…We produced a multi-scale galaxy density map (see Ferrari et al 2005 for more details) using the 550 spectroscopically confirmed cluster members obtained by Owers et al (2009). In Fig.…”
Section: Dynamical Statementioning
confidence: 99%